2008
DOI: 10.1063/1.2953176
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bismuth incorporation on the valence and conduction band edges of GaAs1−xBix

Abstract: We investigate the electronic properties of GaAs1−xBix by photoluminescence at variable temperature (T=10–430K) and high magnetic field (B=0–30T). In GaAs0.981Bi0.019, localized state contribution to PL is dominant up to 150K. At T=180K the diamagnetic shift of the free-exciton states reveals a sizable increase in the carrier effective mass with respect to GaAs. Such an increase cannot be accounted for by an enhanced localized character of the valence band states, solely. Instead, it suggests that also the Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 30 publications
4
47
1
Order By: Relevance
“…On the other hand, type-II band alignment could potentially allow access to longer wavelengths. 10 The band alignment of the GaAsBi/GaAs interface remains uncertain with reports in the literature of type-I, 11,12 type-II, 13 and a nearly flat 14 conduction band offset. In this letter, we investigate the carrier recombination processes of GaAs 1Àx Bi x /GaAs LEDs to aid in the design and optimization of device structures.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…On the other hand, type-II band alignment could potentially allow access to longer wavelengths. 10 The band alignment of the GaAsBi/GaAs interface remains uncertain with reports in the literature of type-I, 11,12 type-II, 13 and a nearly flat 14 conduction band offset. In this letter, we investigate the carrier recombination processes of GaAs 1Àx Bi x /GaAs LEDs to aid in the design and optimization of device structures.…”
mentioning
confidence: 84%
“…In the temperature dependence, we measure the effects both in the CB and valence band (VB), where localization near the VB edge may play a key role for lower temperature dependence. 11 On the other hand, pressure mainly affects the CB, less influenced by Bi. There is no evidence of blue shift with increasing current injection (inset of Fig.…”
mentioning
confidence: 99%
“…III E, we consider the band edge alignment in compressively strained GaBi x As 1−x /GaAs samples. The band alignment at the GaBi x As 1−x /GaAs interface remains uncertain in the literature with reports suggesting that the conduction band offset is of type-I, 2,20,21 or type-II, 14 or nearly flat. 22 Our calculations support a type-I band alignment for all the samples considered.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring electron and hole effective masses provides a potential to unveil physics of hybridization of the Bi-related state with VB and CB. Pettinari et al [215] reported that the exciton mass of GaAs 0.981 Bi 0.019 was derived as 0.088m 0 from magnetic field dependent PL. They considered that both hole and electron effective masses increased and inferred that the localized potential of Bi atoms strongly affected both VB and CB.…”
Section: Effective Massmentioning
confidence: 99%